MARKETING COMMUNICATION POLICY OF AGRARIAN FORMATIONS - GALCHYNSKA, Julia; HRYSHCHENKO, Alla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article deals with the communication policy of agrarian formations, highlighting its main forms. The main elements for the development of a marketing communication policy, as well as the factors that influence these decisions in agriculture, were studied. The role of each element in the overall communication process is presented and the main approaches used in established communication plans are identified. The influence of internal and external environmental factors on the results of current and future agro-forming activities is also shown and evaluated. The key trends in the development of agriculture in the world and in Ukraine were identified, which made it possible to form clear criteria for the development of a marketing communication strategy. The key advantages for the use of marketing tools in agriculture have been determined.In today’s digital age, leveraging digital tools, such as social media platforms, influencer marketing, and content marketing strategies, can enable businesses to connect with consumers on a deeper level. By sharing compelling stories, educational content, and behind-the-scenes insights into sustainable practices by local growers, agribusinesses can build brand loyalty and cultivate a community of engaged consumers. In this context, it is crucial for agribusinesses to tailor their marketing communication strategies to cater to different generational preferences. For instance, research has shown that Generation Y (millennials) are particularly receptive to online information sharing, interactive platforms, and authentic storytelling. By intentionally catering to generational differences and motivations, businesses can effectively resonate with diverse consumer segments and foster lasting connections. Effective marketing communication goes beyond mere promotion; it has the power to shape consumer perceptions of value and ultimately influence purchase intentions. By highlighting the tangible and intangible benefits of sustainable food choices, such as environmental stewardship, health advantages, and support for local communities and economies, agribusinesses can create a compelling value proposition that resonates with conscious consumers and drives sustainable purchasing decisions. Marketing communications are intended to both inform and persuade a target audience, with a view to influencing the behaviour of that group. The behaviour of interest to agribusinesses can range from encouraging farmers to adopt improved husbandry practices or to grow a particular crop (or variety of crop), to encouraging industrial or consumer buyers to try a product or service. As has been said on other occasions, each element of the marketing mix must be designed so as to further the overall marketing strategy, and this includes marketing communications.
Keywords: marketing communication policy; agricultural formation; marketing; strategy; agriculture